Efficient postoperative disposition selection in pediatric otolaryngology patients : a novel approach - Lavin, Jennifer M; Sawardekar, Amod; Sohn, Lisa; Jones, Roderick C; Fusilero, Laurely; Iafelice, Mary E; Molenda, Laura (John Wiley & Sons, 2021)
The publication focuses on efficiency in post-operative and intensive care of pediatric otolaryngology patients. Intended for professional public.
The laryngoscope, ISSN 0023-852X Volume 131, supplementum 1, 2021
Keywords: Child; otorinolaryngologie; Critical Care; Efficiency, Organizational; Treatment Outcome; dětská chirurgie; kvalita zdravotní péče; efektivita organizační; dítě; péče o pacienty v kritickém stavu; pooperační péče; Laryngoscopy; Quality of Health Care; výsledek terapie; laryngoskopie; Postoperative Care